The Transcultural Adaptation and Validation of the Chinese Version of the Duke Anticoagulation Satisfaction Scale - Yibo Wu; Shujie Dong; Xinyi Li; Haiping Xu; Xiaohui Xie (Frontiers Media S.A., 2022)
Background: The Duke Anticoagulation Satisfaction Scale (DASS) offers a method to measure the quality of life and satisfaction of patients taking oral anticoagulants. The study aimed to validate the Chinese version of the DASS in Chinese patients on anticoagulation therapy.Methods: The DASS was translated, back-translated, and transculturally adapted into the Chinese version and then administered to participants taking oral anticoagulants in a physician-pharmacist collaborative anticoagulation clinic at a tertiary teaching hospital from October 2019 to December 2020. Reliability was analyzed through Cronbach's alpha (α) and split-half reliability. Confirmatory factor analysis was performed to test the structural validity of the scale. Exploratory factor analysis was performed for items in the scales using the varimax rotation method.Results: A total of 189 patients completed the Chinese version of the DASS. Four dimensions and 23 items were included, with Cronbach's α values of 0.89, 0.81, 0.89, and 0.74 for limitations on physical activities, diet restrictions, hassles and burdens, and positive psychological effect, respectively. Cronbach's α coefficient of whole scale was 0.91. The split-half reliability of this scale is 0.747 (>0.7).Conclusion: The Chinese version of the DASS indicated excellent reliability and validity, compared to the original version. It could provide a practical instrument for healthcare practitioners to evaluate satisfaction and quality of life for anticoagulated patients in China. The difference in quality of life between patients taking warfarin and novel oral anticoagulants (NOACs) needs to be further explored in future studies.